The Impact of Credit Risk and Bank-Specific Drivers on Banks’ Performance: Evidence from the UAE Region - Ally, Zawadi (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2022)
The COVID-19 pandemic has induced a series of credit risk problems for most commercial banks in the GCC region. Thus, the current paper aims to examine the impact of both credit risk and bank-specific drivers on commercial banks’ financial performance in the UAE from the period 2017 - 2021. The study used NPLs, LLP, and DR as credit risk indicators while CER, LR, and NPLs were used as bank-specific drivers and ROA as financial performance measures. The Random Effect model was used for data analysis. The findings revealed that NPLs and LLP had a negative and significant effect on ROA while CER, LR, and, NPLs were found to have a negative and significant relationship with ROA. This paper implies that banks need remain prudent in their credit risk management and adopt the best strategies to manage and control bank-specific drivers to improve their performance